Diel shifts in the structure and function of nearshore estuarine fish communities. Issue 4 (23rd November 2016) - Yeoh, D. E.; Valesini, F. J.; Hallett, C. S.; Abdo, D. A.; Williams, J.
Abstract : Day–night shifts in the nearshore fish fauna of a temperate microtidal estuary were assessed using a holistic suite of structural and functional community attributes. Mean fish species richness and diversity (taxonomic distinctness) were higher at night across all regions of the estuary and seasons, concurring with the findings of numerous comparable studies reviewed worldwide, while the diel period in which mean abundance was higher varied among seasons. Likewise, species and functional guild compositions (the latter based on feeding modes and habitat use) both differed significantly between day and night, with the extent of the diel shift again varying seasonally. Daytime fish communities were characterized by higher abundances of Atherinidae, Sillaginidae and Mugilidae, while Gobiidae were far more abundant at night. Marked shifts in size composition were also evident, with smaller fishes (<100 mm total length, L T ) being more prevalent during the day and larger fishes (≥200 mm L T ) proportionally more abundant at night. The above diel shifts were feasibly related to a range of predator–prey interactions and feeding‐related movements, namely a nocturnal decrease in top‐order avian piscivory coupled with an increase in invertebrate prey availability, resulting in changes in the presence and catchability of certain fish species in shallow estuarine waters.